Poverty Reduction Efforts in Nepal - Tuladhar, Mina (PYC Nepal Journal of Management, 2015)
Poverty is like curse everyone wants to get rid of. Everyone wants to get rid of the poverty-stricken condition; and countries across the world have individually and collaboratively fighting against the evils of poverty. Based on secondary data, the article has attempted to study the poverty alleviation efforts that Nepal has put up during the period of 1992 to 2013 vis-a-vis the progress Nepal has achieved during the study period for which the study assessed the effort-progress by Nepal’s periodic development plans. Based on the study, the article offers policy recommendation to formulate anti-poverty programmes benefitting dalit and indigenous communities and narrowing down gaps between the rich and the poor.